Pengaruh Edukasi Gizi Dengan Logbook Terhadap Pengetahuan Dan Asupan Remaja Putri Anemia - Aolian Asrori; Abdul Salam; Irianto Irianto; Lalu Khairul Abdi (Poltekkes Kemenkes Mataram, 2020)
Background : Anemia is an unresolved nutritional problem in Indonesia. Data from the Babakan Health Center reported that 19.1% of adolescent girls at SMPN 5 Mataram had anemia, while according to WHO the acceptable threshold was <5%. One of the causes is the lack of knowledge about anemia, low adherence to taking blood booster supplements and there is no media to monitor the intake and adherence. Objectives : The purpose of this study was to analyze